Vessel features of Quercus ilex L. growing under Mediterranean climate have a better climatic signal than tree-ring width - Campelo, Filipe; Nabais, Cristina; Gutiérrez, Emilia; Freitas, Helena; García-González, Ignacio (Trees, 2010)
We investigated whether vessel time series of Holm oak (Quercus ilex L.), a diffuse to semi-ring-porous species, can record a climatic signal which differs from the signal encoded in tree-ring width (TRW). The study was conducted in ten Q. ilex trees from a coppice stand in northeast Spain. Chronologies of TRW, mean vessel area (MVA) and maximum vessel area (MAX) were developed and correlated with climate data, for the period 1985–2004 (20 years). Our results indicate that vessel features contain environmental information that is different from that stored in TRW. MAX chronologies correlate better to early spring precipitation (April–May) than TRW chronologies, and so does MVA of the largest 20–25 vessels from the ﬁrst third of the ring with late spring precipitation (May–June). Also, the combination of MVA and TRW is a better predictor of summer precipitation. This explorative study clearly shows that vessel features can complement the climatic signal of TRW increasing the resolution of the climate reconstructions for the Mediterranean region.
Keywords: Dendrochronology; Holm oak; Mediterranean climate; Tree ring; Vessel features